Entrepreneurs’ Obligations to Disclosure, Recording, Billing, and the Safe-Keeping of Bills with Regard to Vat - Frotscher, Pierre (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
This essay shall give an overview over the entrepreneurs’ obligation to disclose, record, bill and safe-keep bills with regard to VAT. Background is the new regulation of entrepreneurship of the public sector. No later than 1.1.2021, legal entities of public law will largely be treated as equal to private entrepreneurs, and as such, have to observe the formal requirements of VAT law.
Keywords: przedsiębiorca; ujawnienie; ewidencjonowanie; rozliczanie; przechowywanie; faktura VAT